Hydroxylated and methoxylated polybrominated diphenyl ethers in a marine food web of Chinese Bohai Sea and their human dietary exposure. (February 2018) - Liu, Yanwei; Liu, Jiyan; Yu, Miao; Zhou, Qunfang; Jiang, Guibin
Abstract: Hydroxylated (OH-) and methoxylated (MeO-) polybrominated diphenyl ethers (PBDEs) have been identified ubiquitous in wildlife and environment. However, understanding on their trophic accumulation and human exposure was hitherto limited. In this study, the occurrences and trophic behaviors were demonstrated for OH- and MeO-PBDEs using the biota samples collected from Dalian, a coastal city near Chinese Bohai Sea. ∑OH-PBDEs exhibited a wider concentration range (<MDL (method detection limit)–25 ng/g dry weight (dw)) compared with ∑MeO-PBDEs (<MDL–2 ng/g dw) and ∑PBDEs (<MDL–2 ng/g dw). The congener profiles and distribution patterns revealed that majority of OH- and MeO-PBDEs in marine biota were naturally produced and largely attributed to preying on lower trophic level biota. Though tertiary consumers accumulated more MeO-PBDEs and PBDEs, these chemicals did not show statistically significant biomagnification in the selected food web. Conversely, trophic dilution was determined for ortho-substituted OH-tetraBDEs and OH-pentaBDEs, revealing that trophic dilution was prevalent for naturally produced OH-PBDEs. The dietary intake evaluation of OH-PBDEs (0.4 ng/kg/d) and MeO-PBDEs (0.8 ng/kg/d) via seafood consumption showed that coastal residents were in higher exposure risks to OH-PBDEs and MeO-PBDEs via the massive seafood consumption. Graphical abstract: Image 1 Highlights: Naturally produced OH-PBDEs showed trophic dilution in the selected marine food web. MeO-PBDEs and PBDEs accumulated more at high trophic levels, but no significant biomagnification was observed. Algae and invertebrates contributed to the majority of OH- and MeO-PBDEs in marine ecosystem. Seafood consumption was an important exposure pathway of OH- and MeO-PBDEs for coastal residents. Abstract : OH-PBDEs, MeO-PBDEs and PBDEs showed distinct distribution patterns in marine biota. Seafood consumption was an important contributor to human dietary exposure of OH-/MeO-PBDEs.